2015
DOI: 10.1371/journal.pone.0121125
|View full text |Cite
|
Sign up to set email alerts
|

Sex Differences between CRF1 Receptor Deficient Mice following Naloxone-Precipitated Morphine Withdrawal in a Conditioned Place Aversion Paradigm: Implication of HPA Axis

Abstract: BackgroundExtinction period of positive affective memory of drug taking and negative affective memory of drug withdrawal, as well as the different response of men and women might be important for the clinical treatment of drug addiction. We investigate the role of corticotropin releasing factor receptor type one (CRF1R) and the different response of male and female mice in the expression and extinction of the aversive memory.Methodology/Principal FindingWe used genetically engineered male and female mice lacki… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
12
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 55 publications
5
12
1
Order By: Relevance
“…However, CP‐154 526 interrupts naloxone‐induced CPA in morphine‐treated animals suggesting that the consolidation process of opioid‐withdrawn associated aversion could be linked to CRF1 receptor activation. These results are in agreement with previous studies performed in CFR1 knockout mice . In addition, CP‐154 526 administration abolished the acquisition of morphine‐conditioned place preference (CPP) .…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…However, CP‐154 526 interrupts naloxone‐induced CPA in morphine‐treated animals suggesting that the consolidation process of opioid‐withdrawn associated aversion could be linked to CRF1 receptor activation. These results are in agreement with previous studies performed in CFR1 knockout mice . In addition, CP‐154 526 administration abolished the acquisition of morphine‐conditioned place preference (CPP) .…”
Section: Discussionsupporting
confidence: 92%
“…According to previous studies, present results showed that naloxone administration to mice dependent on morphine evoked an increased in body weight loss (0.79 ± 0.04 g) compared with the control group receiving saline instead morphine (0.12 ± 0.06 g; t 14 = 8.369, P < .0001; Student's t test. The body weight loss was accompanied by other withdrawal signs such as ptosis, teeth chattering, tremor, piloerection, lacrimation, rinorrhea, spontaneuous jumping, wet‐dog shakes, salivation, and diarrhea …”
Section: Resultssupporting
confidence: 78%
“…Further work is needed to investigate efficacy against multiple types of nociception (e.g., in models of neuropathic pain, which were not evaluated here) and in a battery of additional models of addiction (such as rodent self‐administration). The ameliorating effects on reinstatement demonstrated here were time‐dependent, but were not evaluated in the context of important factors such as opioid withdrawal and the prolonged dysphoria over time that is associated with reinstatement to morphine‐seeking behaviour (Garcia‐Carmona, Baroja‐Mazo, Milanes, & Laorden, 2015). Further studies evaluating the effects of cyclo [Pro‐Sar‐Phe‐ d ‐Phe] treatment in drug‐responding animals still actively seeking drugs are also important, although beyond the scope of this initial evaluation.…”
Section: Discussionmentioning
confidence: 97%
“…The neural mechanisms that underlie the sexually dimorphic prevalence of these disorders are unclear. Cells that produce corticotropin‐releasing factor (CRF), and those that express the primary receptor for CRF, the G S ‐coupled cognate receptor, CRF receptor 1 (CRFR1), represent intriguing cell phenotypes that might regulate these sex differences, given their known role in regulating anxiety, depression, and stress hormone secretion (Chrousos, ; Da Silva et al, ; Garcia‐Carmona, Baroja‐Mazo, Milanes, & Laorden, ; Holly et al, ; Schussler et al, ).…”
Section: Introductionmentioning
confidence: 99%